(untitled) (Annals of Medical Research, 2024)
Aim: The aim of this study was to evaluate the effects of SARS-CoV-2 vaccines on vestibular system. In addition, in this study we aimed to investigate the possible protective effects of vaccination on the vestibular system in people who recovered Covid-19. Materials and Methods: Totally, 77 subjects were divided into four groups, and evaluated using computerized dynamic posturography (CDP), vestibular evoked myogenic potentials (VEMPs) and video head impulse test (v-HIT). The groups were as follows; Group 1; who had SARS-CoV-2 infection at least one year ago and have not been vaccinated at all. Group 2; who had SARS-CoV-2 infection at least one year ago and were vaccinated 5 times (2 doses of Sinovac and 3 doses of Biontech). Group 3; who had no known SARS-CoV-2 infection, and were vaccinated 5 times (2 doses of Sinovac and 3 doses of Biontech). Group 4; who had no known SARS-CoV-2 infection, and have not been vaccinated at all. Results: The SOT values of (Covid-Vaccine-) group were better than the (Covid+Vaccine-) group (p=0.001), and no other significant difference was found between the groups (p>0.05). The v-HIT gains of the groups were not significantly different (p>0.05). On o-VEMPs, there was elongation in the N1 and P1 latencies in (Covid+Vaccine-) group compared to (Covid-Vaccine+) group. The amplitudes decreased in (Covid+Vaccine-) compared to (Covid-Vaccine-) (p<0.05). According to c-VEMP results, vaccination led to elongation in the P1 latencies and increased the P1-N1 amplitudes (p<0.05). Conclusion: Both SARS-CoV-2 viral infection and vaccination may impact on vestibular system. The impact of vaccination seems on the saccule level. However, vaccination may limit or diminish the impact of SARS-CoV-2 on equilibrium, possibly by facilitating the central compensation.